The Use Of The Application Kahoot In Improving Student Learning Outcomes (Conference on English Language Teaching, 2023)
In principle, E-learning is learning that use electronic service as a tool. Quizizz is one of these E-learning web applications. Quizizz is a competititve games. This application has been widely used by teachers around the world in learning activities, such  as making online quizzes which are currently rife. This study use a quantitative descriptive method through a survei approach that focuses on effectiveness in using Quizizz in teaching english. This research was conducted at the Junior High School Beringin in Deli Serdang district. The subject of this study were 9th grade of Junior High School students in Beringin, totaling 26 students who were studying English with using Quizizz application. The researcher collected data by using a questionnaire, in collecting data the researcher used several method, namely (1) the researcher gave 10 statement related to Quizizz in teaching English, these statements were sent via google drive, (2) then students choose the answer SS, S, TS, STS on the questionaire. To analyze the data the researcher determined the percentage of each questionnaire answered by the students. So the results of this research that average percentage of effectiveness was strongly agree (SS) 53,6%, agree (S) 60,7%, disagree (TS) 39,3%, strongly disagree (STS) 10,7%. The purpose of this study was to determine the effectiveness of using kahoot as a medium for evaluating class VII learning MTS Percut. The type of research used is quantitative descriptive research. Data collection techniques in this study are observation and tests. The data analysis technique used is descriptive using a percentage formula. The subjects in this study were students of grades VII.1, VII.2, VII. 3 and at MTS Percut with a total of 66 people. Based on the results of research in class VII MTS Percut, it was found that the Kahoot application was effectively used as an alternative learning evaluation media at MTS Percut with the average score of observations on the use of Kahoot in grade VII 1 English subjects was in the very good category with a percentage of 100%, grade VII.2 was in the very good category with a percentage of 100% and in VII.3 was in the good category with percentage 80%. In the test results, students were in the good category with an average percentage score of 76.81%.From the results of the study, it can be concluded that the use of Kahoot as a medium for evaluating learning in English subjects in class VII MTS Percut.